2016
DOI: 10.1055/s-0035-1571201
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Stenosis in Neonates with Severe Bronchopulmonary Dysplasia

Abstract: Objectives Pulmonary vein stenosis (PVS) is a rare, often lethal anomaly associated with poor outcomes. Given the association between bronchopulmonary dysplasia (BPD) and cardiovascular complications, we tested the hypotheses that (1) a subgroup of neonates with severe BPD develop PVS (BPD-PVS) and have worse outcomes than do neonates with severe BPD alone (BPD); (2) among a cohort of neonates with severe BPD-associated pulmonary hypertension (BPD-PH), PVS is an additional risk factor for adverse outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
(73 reference statements)
0
40
0
2
Order By: Relevance
“…However, in cases of acquired PVS, initial echocardiogram may show normal pulmonary venous anatomy prior to the development of stenosis, making the diagnosis of PVS particularly difficult. Challenging the diagnosis further, NEC, BPD, and/or severe IUGR can be seen comorbid with PVS [14]. While the gold standard for diagnosis is cardiac catheterization, the risks of this procedure must be taken into consideration and may only be justified with a high index of suspicion, particularly given the frequency of cardiopulmonary morbidities in this population [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in cases of acquired PVS, initial echocardiogram may show normal pulmonary venous anatomy prior to the development of stenosis, making the diagnosis of PVS particularly difficult. Challenging the diagnosis further, NEC, BPD, and/or severe IUGR can be seen comorbid with PVS [14]. While the gold standard for diagnosis is cardiac catheterization, the risks of this procedure must be taken into consideration and may only be justified with a high index of suspicion, particularly given the frequency of cardiopulmonary morbidities in this population [19].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been suggested that vascular mediators such as vascular endothelial growth factor (VEGF) [3, 4, 7] lead to the intimal and medial fibromuscular proliferation seen on vascular pathology [5, 8, 9]. Prematurity and bronchopulmonary dysplasia (BPD) have also been implicated, but at current their specific roles in pathogenesis remain unclear [7, 1014]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si esta condición queda sin diagnóstico, los resultados son peores que en los niños con DBP severa con HP, pero sin estenosis adquirida de las venas pulmonares. (93) Como posibles marcadores de HP en DBP podrían ser de utilidad encontrar elevación de niveles del péptido natriurético alto y niveles bajos de citrulina, un precursor del óxido nítrico. (94) Y un tratamiento podría ser dar L-citrulina, como se menciona antes.…”
Section: Hipertensión Pulmonar (Hp) Por Dbpunclassified
“…Interestingly, a recent study has suggested an association with pulmonary vein stenosis (PVS) with 4.6% of a 213-patient cohort of infants with BPD affected, more frequently those with lower birth weights. Those with associated PVS experienced higher rates of mortality (16). …”
Section: Bronchopulmonary Dysplasia (Bpd)mentioning
confidence: 99%